Efficacy and safety of albendazole alone versus albendazole in combination with ivermectin for the treatment of Trichuris trichiura infections: An open-label, randomized controlled superiority trial in south-western Uganda - Palmeirim, Marta Sólveig; Hürlimann, Eveline; Beinamaryo, Prudence; Kyarisiima, Hilda; Nabatte, Betty; Hattendorf, Jan; Steinmann, Peter; Keiser, Jennifer (PLOS Neglected Tropical Diseases, 2024)
Trichuris trichiura, a soil-transmitted helminth (STH), often persists after a single dose of anthelminthic treatment. To overcome limited efficacy against T. trichiura of benzimidazoles (albendazole or mebendazole), the primary drugs used in mass drug administration (MDA) campaigns, the World Health Organization endorses the use of a combination of ivermectin and albendazole as a more effective treatment to be used for preventive chemotherapy. Given observed considerable differences in efficacy of the combination therapy over albendazole monotherapy between different settings, it is necessary to evaluate the performance of the combination before introducing it on a larger scale. This open-label, randomized controlled superiority trial in two Ugandan primary schools enrolled eligible 6- to 12-year-olds positive for T. trichiura. Participants were randomized 1:1 to receive either a single dose of albendazole alone or co-administered albendazole and ivermectin. Adverse events were monitored at three and 24h post-treatment. Follow-up samples were collected 14 to 21 days post-treatment for efficacy assessment. The combination of albendazole with ivermectin showed superior efficacy against T. trichiura compared to albendazole alone, both in terms of cure rates (31.3% versus 12.3%, difference 18.9%-points, 95% CI 6.2–31.2, p < 0.004) and in terms of egg reduction rates (ERRs; 91.4% versus 52.7%). A higher cure rate against co-infecting Ascaris lumbricoides was observed in the combination compared to the albendazole monotherapy arm (100% versus 83.9%). Both therapies showed an excellent safety profile with few and only mild and transient treatment emergent adverse events observed in the albendazole monotherapy and albendazole plus ivermectin arm (total of 22 and 19 events, respectively). In conclusion, the efficacy of the combination therapy against T. trichiura in Uganda is superior to that of albendazole alone. Given the high ERRs observed, albendazole-ivermectin might aid in eliminating morbidity, an important target of STH control programs. Trial registration (clinicaltrials.gov): NCT06037876.